2014
DOI: 10.1676/13-193.1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in antiparasitic behaviors of Red-winged Blackbirds in response to simulated Brown-headed Cowbirds

Abstract: In response to avian brood parasitism, hosts may develop a number of defenses to reduce the negative consequences parasitism can have on the host's reproductive success. These behaviors may include aggression towards a parasite, rejection of parasitic eggs, or nest desertion. Comparisons of populations that are exposed to parasitism and populations where parasitism is rare or absent may be useful to explain the evolution and maintenance of these behaviors. In a study of American robins (Turdus migratorius) liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…The gene expression responses found here in adult, territorial redwing males in the summer breeding season are different from the IEG patterns detected from juvenile redwing males captured in the fall, which showed that the only conspecific calls generated differential responses in the auditory forebrain relative to cowbird and dove calls 11 . In turn, our behavioral data from adult red-winged blackbirds confirm previous findings in this and other avian hosts of brood parasitic species, which demonstrated behavioral responses to heterospecific parasitic models and auditory stimuli 16,[35][36][37] .…”
Section: Discussionsupporting
confidence: 89%
“…The gene expression responses found here in adult, territorial redwing males in the summer breeding season are different from the IEG patterns detected from juvenile redwing males captured in the fall, which showed that the only conspecific calls generated differential responses in the auditory forebrain relative to cowbird and dove calls 11 . In turn, our behavioral data from adult red-winged blackbirds confirm previous findings in this and other avian hosts of brood parasitic species, which demonstrated behavioral responses to heterospecific parasitic models and auditory stimuli 16,[35][36][37] .…”
Section: Discussionsupporting
confidence: 89%
“…Many host species use both private and social information to assess imminent risk to their nests, the latter of which occurs often by eavesdropping on vocalizations by the threats themselves or the alarm calls of conspecifics (Gill et al., 1997; Gill & Sealy, 2003; Henger & Hauber, 2014; Lawson et al., 2020; Moksnes et al., 1991). Accordingly, hosts of brood parasites have been shown to be able to discriminate between different nest threats (i.e., parasites vs. nest predators) based on their vocalizations, and adjust their defense behaviors accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, yellow warblers themselves respond less aggressively to referential seet calls during the nestling stage likely because there is little to no brood parasitism risk during this stage (Neudorf and Sealy, 1992;Gill and Sealy, 1996), and the same pattern can be seen across other hosts toward models of their respective brood parasites (Fasanella and Fernández, 2009; reviewed in Lawson et al, 2021a). Furthermore, blackbirds presented with taxidermy cowbird and nest predator models across nesting stages respond equally to both models during incubation, but more strongly to the nest predator during nestling stage (Neudorf and Sealy, 1992; also see Henger and Hauber, 2014). To determine whether blackbirds recognize seet calls as referential alarm calls denoting brood parasitism risk, we expanded on our previous playback study conducted during the incubation stage (Lawson et al, 2020), and presented playbacks of cowbird chatters, seet calls, nest predator calls, and a non-threatening control species to blackbird nests during the nestling stage, when the risk of brood parasitism is low.…”
Section: Introductionmentioning
confidence: 81%